PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK MANDIRI SYARIAH - Nurmaysaroh Nurmaysaroh; Sabaruddin Ahmad Dongoran; Yusrizal Efendi Barus; Alinafiah Nasution (Cross-border, 2018)
This study aims to determine and analyze the effect of work discipline on employee performance at PT Bank Syariah Mandiri, the sub-branch office of the tax village of North Labuhanbatu Regency. This research is descriptive. Samples were taken as many as 33 employees of Bank Syariah Mandiri branch office of the tax village of Labuhanbatu Uara Regency. This study aims to see the effect of work discipline, work environment and motivation on employee performance both simultaneously and partially. The results of this study conclude that work discipline, work environment and motivation simultaneously have a significant effect on employee performance at PT. Bank Syariah Mandiri Sub-Branch Office of Tax Village, North Labuhanbatu Regency.